On-board Visualisation of Machining Tool Paths Generated by Function Blocks - Qiao, Qi (Cranfield University, 2014)
A solution for visualising the tool path generated by a function block system is introduced in this research. It facilitates the real-time monitoring of the behaviour of function blocks running on-board a CNC controller, and provides interactivity between the function block system and the shop floor users. In order to improve computer aided process planning for milling operations, a distributed function block system is currently being developed by the project CAPP-4-SEMs (Collaborative and Adaptive Process Planning for Sustainable Manufacturing Environments). In this system, the function blocks are created in a Web-based Distributed Process Planning (Web-DPP) system built in a Cloud environment, and dispatched to CNC controllers to generate complex milling tool paths. This approach is different from the conventional off-line CAD-CAM-CNC approach driven by G-code. The ability of a real-time, on-board visualisation of the behaviour of function blocks is a very important feature for the evaluating and manipulating the behaviour of function block. It helps the users to understand the encapsulated process behaviour which the function block system is generating, and to acquire the confidence that the system is practical and reliable. The aim of this research is to find a suitable solution to realise the visualisation for tool paths generated by a system of function block running on a CNC controller. The existing visualisation methods are researched, compared and selected to fit the purpose. A number of aspects have been investigated such as the program language, graphical user interface layout and the practical needs of the shop floor users. By a requirements survey from industries, the challenging practical needs of industries are collected, analysed and used for steering the development. An application with a 3D graphical user interface has been developed and tested. The developed visualizer is a light weight visualisation tool which is able to run directly on CNC controllers with Windows (or PC with Windows). It can be connected with a Cloud environment (optional) for real-time tool path visualisation.
Keywords: visualisation; function block; tool path; on-board; light weight; real-time; CNC controller